Nonperturbative treatment of a quenched Langevin field theory - Ihssen, Friederike; Pagni, Valerio; Marino, Jamir; Diehl, Sebastian; Defenu, Nicolò (Physical review, 2025)
We present a novel approach within the functional renormalization group framework for computing critical exponents that characterize the time evolution of out-of-equilibrium many-body systems. Our approach permits access to quantities involved in the renormalization procedure, using an expansion about time-translation invariant problems. This expansion can be upgraded to a fully time-dependent computation by iteration. As a prototypical example, we compute the aging exponent 𝜃 describing the dynamics of model A following a sudden quench to the critical point. Already at leading order, the approach demonstrates remarkable accuracy when compared with MC simulations and resummed perturbative expansions in the range 2<𝑑<4. This yields results that surpass those of the two-loop 𝜀 expansion in accuracy and match analytically known benchmarks at large 𝑁. These findings contribute to a deeper understanding of out-of-equilibrium universality and open new avenues for nonperturbative studies of critical dynamics, as well as for exploring the critical behavior of systems with spatial boundaries.
Gesehen am 09.12.2025